Implementation of a Ponseti Clubfoot Program Decreases Major Surgery: A Quality Improvement Initiative. Issue 6 (November 2020) - Carry, Patrick M.; Graham, Susan; Whalen, Karen; Burke, Deborah; Baschal, Robin; Holmes, Kaley S.; Kohuth, Brian; Georgopoulos, Gaia; Miller, Nancy Hadley
Abstract : Introduction: Clubfoot describes a congenital condition. If untreated, clubfoot can cause long-term functional issues. The Ponseti method is the gold-standard treatment; it emphasizes casting over surgery. We identified a high rate of major recurrence in patients with isolated clubfoot at our institution. We implemented a quality improvement intervention to address the recurrences. Methods: We established a clubfoot program that aimed to (1) develop a standardized treatment pathway; (2) improve care team education; (3) improve coordination of care with families; and (4) improve documentation. The purpose of this study was to outline our quality improvement intervention and evaluate its success. Data were retrospectively collected from isolated clubfeet before (2003–2007, phase I) and after (2012–2014, phase II) implementation of the clubfoot program. We compared the differences in treatment and major recurrence between the 2 phases using generalized logistic or linear mixed models. Modified Poisson regression models were used to evaluate the association between provider nonadherence and recurrence. Results: The pre- (phase I) and post- (phase II) implementation groups included 91 patients (131 feet) and 68 patients (101 feet), respectively. The incidence of major recurrence (odds ratio: 59.5, 95% confidence interval: 7.8–454.4, P < 0.0001) was lower during phase II compared to phase I. Nonadherence with the care pathway was associated with an increased risk of recurrence (risk ratio: 4.1, 95% confidence interval: 1.2–14.3, P = 0.0274). Conclusions: The implementation of a clubfoot program was associated with a decrease in major clubfoot surgery and improved adherence to established guidelines for clubfoot management. Abstract : Supplemental Digital Content is available in the text.